Evaluation of Peptic Ulcer Medication Use in Patients with Peptic Ulcer at Inpatient Installation RSUD Sultan Syarif Mohamad Alkadrie - Novi Yana Santika; Rise Desnita; Muhammad Akib Yuswar (Majalah Farmaseutik, 2019)
Peptic ulcer is an upper gastrointestinal tract disease caused by hypersecretion of acids and pepsin of gastric mucosa. Peptic ulcer disease can be caused by several factors such as smoking, fast food, alcoholic beverages, NSAIDs and Helycobacter pylori. The purpose of this research was to obtain the distribution of antiulcer and itsrationality on peptic ulcer inpatients at the RSUD Sultan Syarif Mohamad Alkadrie Pontianak. This study is a descriptive observational study with cross sectional design. Data from medical record collected retrospectively.  This research using medical record peptic ulcer inpatients from January to December in 2017. The samples used were 34 of 44 patients who met  the  inclusion criteria. Based on results, the distribution of anti ulcer were omeprazole (2.94%), pantoprazole (73.53%), lansoprazole (26.47%), ranitidine 5.89%, 58.82% antacids and 85.29% sucralfat. The result of rationality evaluation on criteriaof appropriate indication (100%);appropriate drug (55.88%); appropriate patient (97.06%); and appropriate (61.76%). Overall,the rationality of treatment that meets all four rational treatment criterias was 78.68%.